Government Reform in New Zealand - Scott, Graham (Occasional Papers; Occasional Paper ;, 1996)
New Zealand's reforms of economic policy and public sector management systems have attracted international attention. Beginning in 1984, the country adopted a comprehensive and vigorous program of macroeconomic adjustment that involved redefining the state's role in the economy and social policy. This paper provides an overview of the central frameworks of government management in New Zealand, with particular emphasis on financial management.